Ketiadaan Urgensi Wajib Militer Di Indonesia (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2023)
In the Constitution of the Republic of Indonesia article 30 paragraph (1) Every citizen is entitled and obliged to participate in the defence and security efforts of the state and paragraph (2) The defence and security efforts of the state are carried out through a universal people's defence and security system by the Indonesian National Army and the Indonesian National Police of the Republic of Indonesia as the main force, and the people as a supporting force. This relates to the development of state security and resilience efforts, one of which is the conscription efforts that have been implemented in several countries such as South Korea and Thailand. But military training in Indonesia is only given to the Indonesian National Army, which in essence is something that is directly related to the profession being undertaken. This study uses a descriptive research method which approaches by collecting literature data and analysed by the author. The results of this study confirm that currently Indonesia does not need conscription because it is not in a state of emergency or war for a long period of time so far.